Literacy and attitude of Asian youths on dengue and its prevention in an endemic developed community - Soo, Wern Fern; Gunasekaran, Kalaipriya; Ng, Ding Xuan; Kwek, Kylie; Tan, Ngiap Chuan (Frontiers in Public Health, 2024)
Background Over the past few decades, the incidence of dengue fever has considerably increased. Effective vector control strategies and specific protection using dengue vaccine are thought to be the key elements to combat dengue. The dengue incidence among the Singapore youths (15–24 years) was second only to that of adults (25–44 years). This study evaluated the knowledge and attitude of Singapore youths on dengue and its preventive measures. Methods A cross-sectional study using online-based questionnaire survey was conducted among Singapore youths from September to November 2022. Data were analyzed for descriptive statistics whereas Chi-squared test, linear regression analysis and Pearson correlation were used to determine the association between demographic factors and youth’s attitude on dengue prevention using Rstudio. Results A total of 624 respondents completed the survey out of 1822 surveys distributed nation-wide, with a response rate of 34.2% (mean age 17.4 years ± 1.84; 59.3% female; 89.9% Chinese). The mean dengue knowledge scores of participants were 14.1 ±2.8. Univariate analysis showed that teenagers (15–19 years) had significantly higher knowledge score than the young adults (20–24 years) (β=0.82,95%CI = 0.13–1.51, p = 0.021). Majority of them were aware of the Mozzie Wipeout campaign (90.2%) followed by the release of Wolbachia mosquitos (69.1%). Two-thirds of the youths who were aware of Wolbachia and Gravitrap considered that it was effective in reducing dengue infection rates. Participants suggested information about the current dengue infection rate (71.9%) as the most effective of the five proposed strategies to improve uptake of dengue preventive measures. In comparison to young adults, teenagers were more likely to uptake dengue preventive measures if widespread mosquito control practices were implemented (69.1% vs. 42.3%). Conclusion The overall knowledge of the youths on dengue and its prevention was satisfactory. Future health promotion campaigns targeting the youths should focus on transforming the knowledge into practice.